The Impact of Costumer Experience and Electronic Word of Mouth on Brand Trust - Alya Nursakinah; Afif Zaerofi; Shofi Arofatul Marits (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
This research aims to find out whether there is an influence of customer experience and electronic word of mouth (E-WoM) on brand trust of local skincare products of Z- Generation living in Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek). This research uses a descriptive quantitative approach. To collect the data, a questionnaire is distributed to a total of 145 skincare products users. To analyse the data, multiple linear regression analysis is employed. This research shows that customer experience and E-WoM have a positive significant effect on Brand Trust both partially amd simultinously. Keywords: Customer Experience, E-WoM, Brand Trust